Entre o "real" e o "virtual": representações sociais de internet para sujeitos de duas gerações - Gorza, Marcelo de Souza (2017)
We experience the opening of a new space of interaction and communication in which technologies enable, from one end of the world to the other, human contacts, transmission of knowledge and sociocultural exchange. The internet occupies one of the social spaces of contemporary society, providing a new mobilization between individuals, groups and generations. In this project we address the issue of the Internet as a fundamental element in the organization of actions and interactions of society at the present time. For this, we use the Theory of Social Representations (TSR) as a theoretical-conceptual basis. The objective was to identify the social representations of the Internet, as well as its content, through the discourse of subjects of two generations. The study included 10 dyads of adolescent children and their parents, encompassing both sexes, middle class, who use information and communication technologies (ICT) in their daily lives. We used a semi-structured interview addressing issues that would allow access to the social representations of the internet and to the daily life of the participants. The textual data of the interviews were submitted to the IRAMUTEQ software and Lawrence Bardin's thematic content analysis methodology. The results obtained through IRAMUTEQ allowed the composition and analysis of Hierarchical Descendant Classifications (CHD) of parents and adolescents, separately. The results obtained from the Thematic Content Analysis (codification and categorization of the content of the corpus) allowed the composition of the internet representation in three central thematic axes: 1) Significance about the internet and the role of communication, 2) the social subject And their participation in collective life: the internet and the dynamic inclusion-exclusion and 3) the internet, its social function and the (re) configurations of notions of interaction in time and space. In specific terms of each generational group, for adults, talking about the internet is to refer to a conception linked to the practice of work. The SR content expressed by these adults seems to be based on a more logical, however, more rigid thinking, which leads them to consider themselves as "virtual persons". For teenagers, talking about the internet is to show the naturalness and familiarity with the object. It is to demonstrate how the content of your SR constitutes a knowledge and practice related to study, entertainment and research. It is to make evident how fundamental is the smartphone and social networks, these elements, founders of identity and social insertion. To consider oneself "virtual" subjects means to affirm to be in agreement and in synchrony with the contemporary context; Is belonging. It is also, as a principle of this age, open to the unpredictable, through a dynamic and changeable way of knowing. In short, the SR content found when studying the internet composes its versatile, multifaceted and polyvalent character. It is a representational object loaded with contradictions, which transits in the constant claim between solid and fluid elements. It is an element that interconnects invisible places and links, restructuring conceptions of time and space, leaving doubts as to what would be the transitions of our time. These results allowed us to approach the representational object of the internet in its descriptive and practical/socio-historical aspect, through an approximation to what is understood when talking about the internet, as well as to the way in which the social representation of the same organizes/guides many of the practices.